Application of piezoelectric materials to monitor modulus and strength development of cementitious materials - Lu, Xubin (2018)
Strength monitoring of early-age concrete improves the efficiency of construction as it provides information on the optimum time for shoring removal and pre-stress transferring. Electromechanical impedance (EMI) technique has been proven to be a useful tool for strength monitoring of cementitious materials. One of the key limitations of this technique is the lack of physical models, which resulted in its strong reliance on statistical measures to quantify the strength of structure being monitored.